Effectiveness of Murajaah-Based Tahfidzul Qur'an Learning in Achieving Memorization Targets at MI Annajah I Karduluk Sumenep - Nuriyah, Silfiyatin; Maimun, Ach.; Salamah, Umi (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
This study investigates the effectiveness of Murajaah-based Tahfidzul Qur'an learning in achieving memorization targets at MI Annajah I Karduluk Sumenep. Despite the growing implementation of Tahfidzul Qur'an programs in Islamic elementary schools, empirical evidence on the effectiveness of structured Murajaah practices in achieving measurable memorization targets remains limited. Employing a descriptive qualitative approach, data were collected through participant observation, structured interviews with teachers and the school principal, and document analysis. The findings indicate that the Murajaah-based program, implemented through daily structured repetition sessions and consistent target monitoring, demonstrates effective outcomes as evidenced by 80% of students achieving memorization targets within the designated timeframe. Key supporting factors include high student motivation, disciplined learning schedules, and systematic Murajaah guidance by teachers. Primary challenges encompass limited instructional time, diverse student memory capacities, and insufficient home environment support. These findings suggest that structured Murajaah implementation plays a significant role in determining Tahfidzul Qur'an learning effectiveness at the elementary Islamic school level.